The pertinence of infrastructural facilities in rejuvenation of small scale enterprises in Ikare Akoko , Ondo State, Nigeria - Adejompo Fagbohunka (Economic and Environmental Studies (E&ES), 2016)
The potency of small scale industries in socio economic transformation is awe-inspiring; while inadequate infrastructure poses a gargantuan limitation and a major clog in the wheel of socio- economic revamping. The paper underscores the relevance of infrastructural facilities in rejuvenation of small scale industries, using Ikare Akoko as a case study. The paper adopts a total sampling method; on the whole One hundred and fifteen questionnaires were administered to the proprietors of the small scale enterprises. The paper has reveals a grossly inadequate power supply, which is also regarded as the most germane and influencing infrastructure in the performance of the small scale industries. With the exception of telecommunication, the paper has found out a negative relationship between water supply, effective transportation system, adequate health facilities and the small scale industries. The correlation analysis carried out to test the effectiveness of the infrastructural facilities and the socio economic performance of the small scale industries reveals a non-significant value of 0.799 at 0.005 levels. It was vivid from the research that government has an infinitesimal contribution to infrastructure development of Ikare Akoko. The research reveals the consequences of the unsatisfactory level of infrastructural development such as, low productivity, socio-economic malaise as well as discouragement and lowering the morale of the small scale proprietors. The paper therefore, suggests an integrated approach to infrastructural development at the local, state and federal level. The private sector participation would also contribute to the alleviation of this major bane to the thriving and development of the small scale enterprises.
Keywords: I21; I23; 330; Infrastructural facilities; Small scale industries; Socio-economic performance; Ikare Akoko